Crescimento, produção de betacianina e potencial bioativo de plantas do gênero Alternanthera - Kleinowski, Alítcia Moraes (2011)
The medicinal species of the genus Alternanthera with Alternanthera philoxeroides and Alternanthera tenella feature a variety of bioactive compounds, including flavonoids and betacyanins, pigments with antioxidant properties. Micropropagation can contribute to the study of bioactive plants it provides controlled growing conditions and permit the use of exogenous precursors or elicitors of the biosynthesis of substances of interest. Other promising tools in the study of medicinal plants are the tests to verify the bioactive potential of these species, using bioindicators. This work aimed to study the growth, production betacyanins and potential bioactive plant of the genus Alternanthera. In vitro experiments, nodal segments were inoculated on MS medium with different concentrations of tyrosine (0, 25, 50 and 75 μM). Plants were evaluated on the number of shoots and buds, height, root length, fresh weight of part shoots and roots and content betacyanin. In the species A. philoxeroides among the variables analyzed, only to shoot high, the highest concentration, showed a significant decrease. The root was affected from the first concentration occurring a decrease in the length of which the concentration of 75μM no formation of this organ. Betacyanin production in all treatments was higher in stem than leaf. For the testing of bioactive species A. philoxeroides extracts were obtained by maceration of dried leaves and stems, with subsequent liquid-liquid partition with solvents of increasing polarity (hexane, dichloromethane, ethyl acetate, butanol). Germination tests were performed with solutions of 0; 1,0; 2,0 e 3,0mg mL-1 with 30 seeds of lettuce and four replications. The antibacterial activity was evaluated by disc diffusion technique was tested where the sensitivity of five reference strains, with the extracts at a concentration of 100mg mL-1 .The ethyl acetate extract obtained from leaves at the highest concentration influenced only in the germination of lettuce, while the force was significantly affected by all extracts at concentrations of 1.0 mg mL-1. None of the extracts of A. philoxeroides the concentration tested interfered with the growth of the strains used. Variables in vitro growth of A. tenella showed a decrease in their average with increasing concentrations of tyrosine and the concentration of 75μM was toxic. However betacyanin production was enhanced with the addition of 50μM of the compound in the culture medium. These results demonstrate the positive effect of elicitation with the production of tyrosine betacyanin in both species, but applications in high concentrations are deleterious to plant growth